The characteristics of assessment tools in the built environment: heritage buildings - Mat Hasan, Hasni Suryani; Ab Wahab, Lilawati; Ismail, Dzulkarnaen; Abdul Rahim, Puteri Rohani Megat; Mat Hasan, Hasni Suhana (GADING Journal for the Social Sciences, 2022)
An assessment is a technique for evaluating a building's performance or output using a set of criteria or indicators. In the built environment, there are several assessments to conserve heritage buildings that have been started by the government. These evaluations are diverse from one another and serve different purposes during the planning, starting, middle, and end phases of construction or conservation. The value of the building and its performance are evaluated as part of the assessments of the built environment. The objective of the study is to identify the characteristics of assessment tools in the built environment, focusing on heritage buildings. In order to achieve the objective, the data was obtained from previous literature, including journals and theses. The findings reveal that the characteristics of assessments in the built environment focused solely on descriptive assessments rather than numerical assessments. In contrast to descriptive assessments, numerical assessments' parameters produce more precise data on performance value and are easier to control. This study also found that the assessments focus on the threats, significance, or impacts of properties that collectively comprise the 'historic' values, as well as a heavy emphasis on the sustainability, performance, and condition of each individual building unit. The outcome of the study is hoped to be a future reference for organisations or individuals interested in assessment rating tooIs in the built environment, focusing on heritage buildings.